THE INFLUENCE OF CREDIT RISK, CAPITAL ADEQUACY AND LIQUIDITY TOWARD PROFITABILITY AND STOCK VALUATION OF COMMERCIAL BANKS BUSINESS ACTIVITIES 4 BEFORE AND DURING COVID-19 PANDEMIC - Arum Sabarina, Rahmafitri
The global pandemic COVID-19, the outbreak triggered unprecedented situations. This massive impact not only on human health, but also on economic consequences. Banks have functions in distributing public aid by providing credit to household and corporate sector. During pandemic COVID-19, bank cannot provide their maximum function due to the impact on economic activity. Much research has been conducted due to analyze the effect of COVID-19 to the banking sector and banks with weak capital position, low profitability and worse quality of the credit portfolio are sensitive to COVID-19. This paper aimed to examine the influence of credit risk, capital adequacy and liquidity toward profitability and stock valuation of commercial banks business activities 4 during COVID-19 pandemic. Limitations were made to narrow down the paperwork, limitations of this paper were Commercial Bank Business Activities 4, listed bank in Indonesia Stocks Exchange, the timeframe for Q1 2016 – Q1 2022. Credit risk will be evaluated in this paper by using Non-Performing Loan (NPL) and allowance for impairment losses (CKPN) data. Liquidity, capital adequacy and profitability will be analyzed in this paper by using some financial performance variables such as Loan to Deposit Ratio (LDR), Capital Adequacy Ratio (CAR), Return on Asset (ROA), Return on Equity (ROE). Stock valuation will be evaluated in this paper by using Price to Book Value (PBV), Price Earnings Ratio (PER) and Earning per Share (EPS)All of data collection were analyzed by using GSCA to find the correlation of each factor. From the data collected during COVID-19 shows a decrease of NPL value for -0,22%, an increase of CKPN value for 1,56%, an increase of CAR value for 0,97%, a decrease of LDR for -7,90%, a decrease of ROA for 0,62%, a decrease of ROE for 2,79%, a decrease of NIM for 0,81%, a decrease of PER for 0,806%, a decrease of EPS for 27,81, a decrease of PBV for 1,46%. From the data collected, it shows the decline in banking performance both financially and in the assessment of investors. In order to compare the differences in conditions, two tests were carried out for the data that had been collected. The first test was carried out for data before COVID-19, with a FIT validation value of 66.7% and AFIT of 60.8%. The second test was carried out for data during COVID-19, with a FIT validation value of 78.3% and AFIT of 71.3%. Through GSCA testing, it was found that the results were the same before COVID-19 and during COVID-19, namely the correlation between (1) credit risk to profitability, (2) capital adequacy to profitability, (3) credit risk to bank stock valuation, (4) liquidity to bank stock valuation, and (5) capital adequacy to bank stock valuation. Investors evaluated indicators of credit risk, liquidity, and capital adequacy to invest in banks, even though these three indicators are not a reference, but they affect investor confidence. The interesting thing is that there is a difference in the correlation between liquidity and profitability, before COVID-19 it was negative and not significant and when COVID-19 showed a significant positive, the difference was affected by the restructuring policy of the Financial Services Authority. Differences were also found in the correlation of profitability to bank stock valuations, where during COVID-19 the results were negative and insignificant. The reason is that during COVID-19, investors withheld investment activities due to the uncertainty of economic conditions.